PERSPEKTIF PSIKOLOGI PERKEMBANGAN DAN PENDIDIKAN ANAK USIA DINI DALAM MEMBANGUN KARAKTER KEJUJURAN: (TINJAUAN LITERATURE INTEGRATIF) - Mathilda Monalisa Marbun (SOSCIED, 2026)
Honesty is a foundational character strength, yet dishonesty in young children cannot be interpreted only as moral failure because it develops together with language, theory of mind, and executive function. This study examines the developmental mechanisms of honesty, evaluates relevant educational strategies, and proposes an applicable model for Indonesian early childhood education. An integrative literature review was conducted by selecting 26 theoretical, review, and empirical sources published mainly between 2013 and 2026 through PubMed, Google Scholar, Garuda, and journal portals. The sources were analyzed thematically according to developmental mechanisms, pedagogical practices, and ecological contexts. The synthesis indicates that fear-based punishment is less effective than autonomy-supportive moral explanations, safe responses to children’s admissions, consistent adult modeling, habituation, positively framed stories, guided play, and reflective dialogue. Honesty education also requires alignment among family, school, and community because contradictory adult practices weaken value internalization. The article proposes a four-layer model consisting of individual moral understanding and self-regulation, relational modeling and dialogue, psychologically safe classroom practices, and ecological consistency through the Tri Pusat Pendidikan and Pancasila values. The model provides operational indicators for curriculum planning, classroom assessment, teacher development, and parent-school collaboration. Empirical testing across diverse Indonesian early childhood settings is recommended.